Unequal Eye: A Case of Unilateral High Myopia and Anisometropia Amblyopia - Umboh, Anne S. M.; Tansil, Alberta Y. M. (e-CliniC, 2025)
Abstract: Myopia, or nearsightedness, is a common eye condition. Unilateral myopia, where only one eye is nearsighted, poses unique challenges. The causes are complex, involving both genetics and environment. Treatment options include glasses, contact lenses, and surgery. We reported a case of a 13-year-old girl with unilateral high myopia and anisometropic amblyopia in her right eye. Despite no family history of myopia, the patient developed severe myopia in her right eye at the age of 7. A comprehensive ocular assessment was conducted, along with auxiliary tests. The patient was diagnosed with unilateral high myopia and anisometropia amblyopia. Treatment included a combination of spectacle correction, soft contact lenses, atropine eye drops, and patching therapy. Unilateral high myopia requires a thorough evaluation. The difference in eye length between the two eyes contributed to the patient’s nearsightedness. Treatment options include glasses, contact lenses, orthokeratology, and surgical procedures. The patient received a personalized treatment plan with regular follow-up to monitor progress and assess treatment efficacy. In conclusion, this case underscores the importance of early detection and aggressive management of high myopia in pediatric patients to prevent further visual deterioration and potential complications. Keywords: unilateral high myopia; amblyopia; anisometropia; management myopia